Emocje jako element kultury używania słowa pisanego w służbach specjalnych na przykładzie relacji MSW i Stasi - przyczynek do dyskusji nad problemem - Jaskułowski, Tytus (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
When studying the activities of secret services, the role of emotions in the use of the spoken and the written word in the work of the said entities is often forgotten. Meanwhile, the primary function of the secret service, namely supplying information to policymakers, is nothing more than communication through the written word conveying nothing other than a range of various emotions. In addition to the purely informational function, these emotions contain threads of inspiration, grotesque, or even disinformation.
Keywords: emocje; słowo pisane; wywiad; kontrwywiad; PRL; NRD; emotions; written word; intelligence; counterintelligence; Polish People`s Republic; GDR